PEMANFAATAN PUPUK ORGANIK UNTUK MENINGKATKAN HASIL PANEN TANAMAN JAGUNG DI DESA CAMPA KECAMATAN MADAPANGGA - Adi Syamsurizal; Edi Sutoyo (JPMUJ, 2023)
Utilization of organic fertilizers is one of the efforts to provide learning experiences or create a new condition in the community environment, by opening avenues of communication and providing information, to increase knowledge in providing understanding regarding the use of organic fertilizers through approaches to Village Heads, farmer groups and communities, so that they can apply methods of using organic fertilizers to increase yields of corn crops for the people of Campa Village, Madapangga District. In this study the approach method used was a direct approach, namely by visiting residents' homes one by one and then distributing questionnaires using the Simple Random Sampling technique. The purpose of distributing the questionnaire was to find out the intellectual community regarding the use of organic fertilizers properly and correctly in increasing the yield of the community's corn crops. The results of this study are that the level of knowledge of the people of Campa Village, Madapangga District regarding the use of organic fertilizers is still low or it is counted as much as 45% are fulfilled, 75% of respondents answered that they did not know about the use of organic fertilizers and in the next statement that tested the knowledge of respondents regarding the types of organic and inorganic fertilizers it was stated only about 35% know the difference in the type of fertilizer. When viewed from the statement above, this shows that the level of public knowledge regarding the types of organic fertilizers is still relatively low.